Proceedings of the Comprehensive Oncology Network Evaluating Rare CNS Tumors (NCI-CONNECT) Adult Medulloblastoma Workshop. Issue 1 (17th August 2020) - Penas-Prado, Marta; Theeler, Brett J; Cordeiro, Brittany; Dunkel, Ira J; Hau, Peter; Mahajan, Anita; Robinson, Giles W; Willmarth, Nicole; Aboud, Orwa; Aldape, Kenneth; Butman, John A; Gajjar, Amar; et al.
Abstract: Background: Medulloblastoma (MB) is a rare brain tumor occurring more frequently in children in whom research has been primarily focused. Treatment recommendations in adults are mainly based on retrospective data and pediatric experience; however, molecular features and treatment tolerance differ between the 2 age groups. In adults, prognostic tools are suboptimal, late recurrences are typical, and long-term sequelae remain understudied. Treatment has not adapted to molecular classification advances; thus, the survival rate of adult MB has not improved. Methods: In 2017, the National Cancer Institute (NCI) received support from the Cancer Moonshot℠ to address the challenges and unmet needs of adults with rare central nervous system tumors through NCI-CONNECT, a program that creates partnerships among patients, health care professionals, researchers, and advocacy organizations. On November 25, 2019, NCI-CONNECT convened leading clinicians and scientists in a workshop to review advances in research, share scientific insights, and discuss clinical challenges in adult MB. Results: Working groups identified unmet needs in clinical trial design, tissue acquisition and testing, tumor modeling, and measurement of clinical outcomes. Conclusions: Participants identified opportunities for collaboration; discussed plans to create a working group of clinicians, researchers, and patient advocates; and developed specific action items to expedite progress in adult MB.